Pengaruh Vaksinasi COVID-19 terhadap Kesehatan dan Kondisi Ekonomi Masyarakat di Indonesia - Lestari, Ayu; Zen, Fauziah (UI Scholars Hub, 2025)
The COVID-19 vaccination is considered crucial for controlling the pandemic and accelerating economic recovery. However, empirical evidence on the impact of vaccination on health and the economy at the district/city level in Indonesia remains limited. This study aims to analyze the impact of vaccination on health outcomes and economic conditions. The methodology used is a fixed effect model with monthly panel data on vaccination and health outcomes (positivity rate and recovery), as well as annual data on per capita expenditure in 514 districts/cities from January 2021 to December 2022. The results show that the first dose of vaccination significantly reduces the positivity rate, increases recovery rates, and enhances per capita expenditure. Furthermore, the second dose of vaccination sustains these positive effects, underscoring the importance of complete vaccination doses.